Prediction of attitude towards infidelity based on the role of dark dimensions of personality, self-differentiation and sexual attitude in women divorce applicants - Yousef Pouri, Mina; Bahrami, Bita (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The main purpose of the present research is to predict the attitude towards infidelity based on the role of dark personality traits, self-differentiation, and sexual attitudes in individuals seeking divorce. Method: This research is descriptive-survey and correlational in nature. The statistical population included women seeking divorce who visited welfare centers in District 6 of Tehran in the autumn 2022. A total of 230 individuals were selected through convenient sampling. Data were collected using the Whatley Marital Infidelity Attitude Scale (2006), the Johnson and Webster Dark Triad Personality Trait Questionnaire (2010), the Skowron and Smith Self-Differentiation Questionnaire (2003), and the Khoshabi and Valaie Sexual Attitude Questionnaire (2018). Data analysis was performed in two sections, descriptive and inferential, using Pearson correlation and multivariate regression analysis. Results: The results showed that dark personality traits, self-differentiation, and sexual attitudes have a significant impact on the attitude towards infidelity. Conclusion: It can be concluded that dark personality traits, self-differentiation, and sexual attitudes are influential factors in the attitude towards infidelity.